African Swine Fever Outbreak at a Farm in Central Namibia - Alaster Samkange; Borden Mushonga; Douglas Mudimba; Bernard A. Chiwome; Mark Jago; Erick Kandiwa; Alec S. Bishi; Umberto Molini (Case Reports in Veterinary Medicine)
An outbreak of African swine fever (ASF) occurred at a farm in central Namibia in March 2018. Fourteen pigs died out of a herd of 59 animals over a period of 16 days between the first and sixteenth of March 2018. The clinical signs observed included sternal recumbency, fever, weakness, pain and reluctance to move, hyperemia of the skin and anorexia, followed by death. Necropsy findings included large amounts of unclotted blood in the pleural and peritoneal cavities, diffuse carcass congestion, splenomegaly, consolidation of both lungs, hemorrhagic and frothy airways and trachea, hepatomegaly and congestion, congestion of the gastric mucosa, enlarged and congested kidneys, ecchymotic epicardial, and endocardial hemorrhages, and very enlarged and congested urinary bladder. All the remaining pigs were euthanized, burned, and buried under state veterinary supervision. The authors concluded that the outbreak resulted from indirect transmission of the ASF virus due to lapses in biosecurity measures.